2019
DOI: 10.1111/soin.12347
|View full text |Cite
|
Sign up to set email alerts
|

“We're the Normal Ones Here”: Community Involvement, Peer Support, and Transgender Mental Health

Abstract: This article uses ethnographic methods to explore how peer support and community involvement influence the mental health and well-being of transgender (or, trans) people in the southeastern United States. The study builds on existing research that suggests that trans community involvement and peer support among trans people enhance mental health experiences and moderate the effects of stigma and discrimination on health outcomes. Through qualitative analysis of 158 hours of participant observation and 33 indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 52 publications
(74 reference statements)
4
24
0
1
Order By: Relevance
“…Mental health inequalities are even more pronounced within some LGBTQ subcommunities. People with trans histories, for example, experience exceptionally high levels of suicidality (Johnson & Rogers, 2020 ). The largest study to date of young trans and gender diverse people in Australia (those aged between 14 and 25) found that almost half of the 859 participants had made attempts at taking their own life (Strauss et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health inequalities are even more pronounced within some LGBTQ subcommunities. People with trans histories, for example, experience exceptionally high levels of suicidality (Johnson & Rogers, 2020 ). The largest study to date of young trans and gender diverse people in Australia (those aged between 14 and 25) found that almost half of the 859 participants had made attempts at taking their own life (Strauss et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Funding for community-led organisations, informed by lived experience, is an essential step in overcoming these barriers. 57 This has been modelled by the Translatin@ coalition, which combats violence and the incarceration and marginalisation of transgender people across the USA through community programmes. 58,59 Community-led organisations provide practical and emotional support and opportunities to cultivate individual resilience in the form of hope, self-affirmation, connection and purpose.…”
Section: Living With Intersecting Layers Of Violencementioning
confidence: 99%
“…Research also finds that cisgender people often draw upon religious, scientific, and media representations of a cisgender‐only society to demonize transgender people and justify opposition to transgender civil rights (Mathers, Sumerau, and Cragun 2018). Such educational and cultural representations also provide medical practitioners with vocabularies of motive for denying care to transgender patients (see, e.g., Johnson and Rogers 2020; Pearce 2018; Shuster 2016). Further, statistical analyses confirm these findings by demonstrating less acceptance of transgender people (as compared to other minority groups) among both religious and nonreligious individuals (Cragun and Sumerau 2017), and systemic medical disparities in access and care for transgender people (Miller and Grollman 2015).…”
Section: Vocabularies Of Motivementioning
confidence: 99%